Influence of Gold Nanoparticles on the Kinetics of α-Synuclein Aggregation - Alvarez, Yanina Daniela (2013)
α-synuclein (AS) is a small (140 amino acids), abundant presynaptic protein, which lacks a unique secondary structure in aqueous solution. Amyloid aggregates of AS in dopaminergic neurons of the midbrain are the hallmark of Parkinson's disease (PD). The process of aggregation involves a series of complex structural transitions from innocuous monomeric AS to oligomeric, presumably neurotoxic, forms and finally to fibril formation. Despite its potential importance for understanding PD pathobiology and devising rational, targeted therapeutic strategies, the details of the aggregation process remain largely unknown. Methodologies and reagents capable of controlling the aggregation kinetics are essential tools for the investigation of the molecular mechanisms of amyloid diseases. In this work, we investigated the influence of citrate-capped gold nanoparticles on the aggregation kinetics of AS using a fluorescent probe (MFC) sensitive to the polarity of the molecular microenvironment via excited state intramolecular proton transfer (ESIPT). The particular effects on the half time, nucleation time, and growth rate were ascertained. Gold nanoparticles produced a strong acceleration of protein aggregation with an influence on both the nucleation and growth phases of the overall mechanism. The effects were dependent on the size and concentration of the nanoparticles, being strongest for nanoparticles 10 nm in diameter, which produced a 3-fold increase in the overall aggregation rate at concentrations as low as 20 nM.